Evaluasi Penerapan Peresepan Elektronik (E-Prescribing) di Rumah Sakit Roemani Muhammadiyah Semarang: Evaluation of Electronic Prescribing (E-Precribing) Implementation At Roemani Muhammadiyah Hospital Semarang - Niken Dyahariesti; Ayang Rizky Safitri Utami (Universitas Ngudi Waluyo, 2024)
ABSTRACT Electronic prescribing is an information technology innovation in health care that can improve service quality, but its implementation still faces challenges that require evaluation, especially at Muhammadiyah Roemani Semarang Hospital, which has been implementing this system since 2016. This study aims to evaluate the implementation of the electronic prescribing system at Roemani Hospital based on the availability of its features. This study is a descriptive qualitative research. The sampling technique used was purposive sampling. Respondents used 4 pharmacists. Data collection was carried out with an observation sheet by the pharmacist followed by a confirmation interview with the pharmacist. The results of the interview were transcribed into text, coding at each point and drawing conclusions. Electronic prescribing in the hospital is quite complete and running well, with 87.5% feature completeness from the Indonesian Ministry of Health. The hospital has implemented 57.7% of the recommended features in international journals, but some obstacles still need to be overcome, such as slow internet network problems, differences in drug stocks, and non-compliance of prescription writers. The electronic prescribing system at Roemani Muhammadiyah Hospital is generally running well, but still needs improvement in several aspects to further optimize the performance and benefits of the system. ABSTRAK Peresepan elektronik merupakan inovasi teknologi informasi di pelayanan kesehatan yang dapat meningkatkan kualitas pelayanan, namun penerapannya masih menghadapi tantangan sehingga perlu dilakukan evaluasi, khususnya di Rumah Sakit Muhammadiyah Roemani Semarang yang telah menerapkan sistem ini sejak 2016. Penelitian ini bertujuan untuk mengevaluasi penerapan sistem peresepan elektronik di Rumah Sakit Roemani berdasarkan ketersediaan fiturnya. Penelitian ini merupakan penelitian deskriptif kualitatif. Teknik sampling yang digunakan purposive sampling. Responden yang digunakan 4 apoteker. Pengambilan data dilakukan dengan lembar observasi oleh Apoteker dilanjutkan dengan wawancara konfirmasi dengan Apoteker. Hasil wawancara ditranskripsi ke dalam teks, pengkodean pada tiap point dan penarikan kesimpulan. Peresepan elektronik di Rumah Sakit sudah cukup lengkap dan berjalan dengan baik, dengan kelengkapan fitur 87,5% dari Kemenkes RI. Rumah sakit ini telah menerapkan 57,7% dari rekomendasi fitur pada jurnal internasional, tetapi beberapa kendala yang masih perlu diatasi, seperti masalah jaringan internet yang lambat, perbedaan stok obat, serta ketidakpatuhan penulis resep. Sistem peresepan elektronik di Rumah Sakit Roemani Muhammadiyah secara umum sudah berjalan dengan baik, namun masih memerlukan perbaikan pada beberapa aspek agar lebih mengoptimalkan kinerja dan manfaat sistem